An in vitro study on the mechanisms of coagulation activation in acute myelogenous leukemia (AML): role of tissue factor regulation by cytotoxic drugs and GM-CSF - Langer, Florian; Amirkhosravi, Ali; Loges, Sonja; Meyer, Todd; Eifrig, Barbara; Hossfeld, Dieter K.; Fiedler, Walter; Francis, John L. (Thrombosis and Haemostasis, 2004)
AML patients may suffer from a disseminated coagulopathy, which can aggravate a pre-existing bleeding tendency due to thrombocytopenia and platelet dysfunction. The cellular and molecular mechanisms underlying this coagulopathy, however, are not completely understood. Indeed, the broad and increasing therapeutic use of cytotoxic drugs and growth factors is likely to contribute to the complexity of hemostatic abnormalities encountered in this hematologic malignancy. The nature of coagulation activation in AML was therefore investigated in vitro using the human leukemic cell line, HL60. Tissue factor (TF) was almost entirely located on the cell surface and bound factor VIIa, but only 15-25% of this TF was primarily functionally active. Treatment with increasing concentrations of daunorubicin or cytosine-β-D-arabinofuranoside, two cytotoxic drugs commonly used in AML therapy, induced apoptosis and secondary necrosis of HL60 cells and resulted in marked decryption of TF PCA independent of de novo protein synthesis. This PCAmodulating effect was concomitant with and functionally dependent on the exposure of phosphatidylserine on the outer membrane leaflet. Similar observations were made in analogous ex vivo studies on patient-derived myeloblasts. Incubation of HL60 cells with GM-CSF, a cytokine expressed in the bone marrow microenvironment and used as an adjunct to AML treatment, evoked a cellular response, which included both enhanced TF production and release of VEGF-A and uPA into the culture medium. We conclude that both decryption of preformed TF PCA by chemotherapeutic drugs and de novo induction of TF by cytokines such as GM-CSF can regulate the procoagulant phenotype of HL60 cells in vitro.
Keywords: Tissue factor / factor VII; apoptosis; disseminated intravascular coagulation (DIC) / sepsis; malignancy; cytokines